Polybutylene terephthalate resin composition and molded article comprising the same
The PBT resin composition, formulated with specific amounts of brominated flame retardant, antimony compound, and glass fiber, achieves enhanced mechanical properties, flame retardancy, and fluidity, overcoming the challenges faced by conventional PBT resin compositions.
Patent Information
- Application Number
- JP2023194806
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-11-16
- Publication Date
- 2025-05-28
AI Technical Summary
Conventional polybutylene terephthalate (PBT) resin compositions face challenges in achieving excellent fluidity during injection molding while maintaining high flame retardancy and mechanical properties, particularly due to the use of high molecular weight PBT and insufficient glass fiber content.
A PBT resin composition is developed by blending 20 to 40 parts by weight of a brominated flame retardant with a weight average molecular weight of 1000 to 5000, 6.0 to 15.0 parts by weight of an antimony compound, and 100 to 200 parts by weight of glass fiber with 100 parts by weight of a PBT resin having an intrinsic viscosity of 0.50 to 1.00 dL/g.
The resulting PBT resin composition exhibits excellent mechanical properties, high flame retardancy, and improved fluidity during injection molding, effectively addressing the limitations of previous technologies.
Smart Images

Figure 2025081802000001
Abstract
Description
Technical Field
[0001] The present invention relates to a polybutylene terephthalate resin composition having excellent fluidity, high flame retardancy and mechanical properties, which is useful for applications such as electrical and electronic equipment parts, automotive parts, and mechanical parts, and a molded article formed by molding the same.
Background Art
[0002] Polybutylene terephthalate resin (hereinafter sometimes abbreviated as PBT resin) is excellent in heat resistance, chemical resistance, electrical properties, dimensional stability, etc., and thus is widely used as a material for manufacturing various electrical and electronic equipment parts, vehicle parts such as automobiles and trains, mechanical parts, and other general industrial products.
[0003] However, since PBT resin is inherently flammable, in addition to the general chemical and physical property balances, safety against fire, that is, flame retardancy, is required for use as the above industrial materials such as electrical and electronic equipment parts and automotive parts, and high flame retardancy showing V-0 of the UL-94 standard is often required.
[0004] In addition, among the above various electrical and electronic equipment parts, automotive parts, mechanical parts, etc., in order to form molded articles with a thin wall and a complex shape such as breakers, housings, electromagnetic switches, coil bobbins, relays, capacitors, etc., excellent fluidity, high flame retardancy, and mechanical properties may be required.
[0005] For example, Patent Document 1 exemplifies a method of blending a flame retardant, glass fiber, and glass flake with PBT resin to impart flame retardancy and mechanical properties. Patent Document 2 exemplifies a method of blending a flame retardant, a reinforcing fiber having a flat shape and a long fiber length, and a flame retardant with a thermoplastic resin to impart flame retardancy and mechanical properties. Patent Document 3 exemplifies a method of blending a flame retardant and a fibrous basic magnesium sulfate compound with an aromatic polyester resin to impart flame retardancy and mechanical properties.
Prior Art Documents
Patent Document
[0006]
Patent Document 1
Patent Document 2
Patent Document 3
Summary of the Invention
Problems to be Solved by the Invention
[0007] However, in Patent Document 1, there is no description regarding flame retardancy and the compounding amount of glass fiber. Furthermore, since the content of glass fiber was small, the mechanical properties were insufficient. In addition, the brominated acrylate oligomer, which is a flame retardant, has a high molecular weight, so there was a problem that the fluidity during injection molding was significantly reduced. In Patent Document 2, the length of the glass fiber in the resin composition was as long as 1 mm or more, and the pentabromobenzyl polyacrylate, which is a flame retardant, has a high molecular weight, so there was a problem that the fluidity during injection molding was significantly reduced. In Patent Document 3, a PBT resin with a high molecular weight is used to improve flame retardancy, but the fluidity during injection molding is not sufficient. Also, the reinforcing effect of the fibrous basic magnesium sulfate compound was not sufficient, and there were problems with the mechanical properties.
[0008] In order to improve the flame retardancy of polybutylene terephthalate resin, it is common to use a polybutylene terephthalate resin with a high molecular weight and a flame retardant. However, when the molecular weight is high, a decrease in fluidity is inevitable, and it does not have good mechanical properties. Also, in order to improve the mechanical properties of polybutylene terephthalate resin, it is known to compound a fibrous filler, but there was a problem that the fluidity during injection molding decreased.
[0009] As described above, there is a demand for a polybutylene terephthalate resin composition that has excellent fluidity during injection molding while maintaining high flame retardancy and mechanical properties. However, the conventional technology could not sufficiently meet this requirement.
[0010] In view of the above problems, an object of the present invention is to provide a polybutylene terephthalate resin composition having excellent fluidity, high flame retardancy, and mechanical properties by blending a specific flame retardant and a large amount of glass fiber with a polybutylene terephthalate resin having a specific viscosity.
Means for Solving the Problems
[0011] As a result of repeated studies to solve the above problems, the present inventors have found that the above problems can be solved by blending a specific amount of (B) a brominated flame retardant having a weight average molecular weight of 1000 to 5000, (C) an antimony compound, and (D) glass fiber with (A) a polybutylene terephthalate resin having an intrinsic viscosity of 0.50 to 1.00 dL / g, and thus have reached the present invention. That is, the present invention has the following configurations. 1. A polybutylene terephthalate resin composition comprising 20 to 40 parts by weight of (B) a brominated flame retardant having a weight average molecular weight of 1000 to 5000, 6.0 to 15.0 parts by weight of (C) an antimony compound, and 100 to 200 parts by weight of (D) glass fiber based on 100 parts by weight of (A) a polybutylene terephthalate resin having an intrinsic viscosity of 0.50 to 1.00 dL / g. 2. The polybutylene terephthalate resin composition according to item 1, wherein the (C) antimony compound is antimony trioxide. 3. The polybutylene terephthalate resin composition according to item 1 or 2, wherein the (B) brominated flame retardant having a weight average molecular weight of 1000 to 5000 is at least one selected from a brominated polycarbonate compound and a brominated epoxy compound. 4. The polybutylene terephthalate resin composition according to any one of items 1 to 3, wherein the blending amount of (B) glass fiber is 125 to 175 parts by weight based on 100 parts by weight of (A) a polybutylene terephthalate resin having an intrinsic viscosity of 0.50 to 1.00 dL / g. 5. The polybutylene terephthalate resin composition according to any one of claims 1 to 4, which is obtained by further blending 1.0 to 2.0 parts by weight of (E) a dripping inhibitor with 100 parts by weight of a polybutylene terephthalate resin having an intrinsic viscosity (A) of 0.50 to 1.00 dL / g. 6. A molded article comprising the polybutylene terephthalate resin composition according to any one of claims 1 to 5.
Advantages of the Invention
[0012] According to the present invention, it is possible to obtain a polybutylene terephthalate resin composition that not only has excellent mechanical properties but also excellent fluidity during injection molding while maintaining a high level of flame retardancy by a flame retardant and a large amount of glass fiber.
Embodiments for Carrying Out the Invention
[0013] Next, the polybutylene terephthalate resin composition of the present invention will be described in detail.
[0014] The polybutylene terephthalate resin composition of the present invention is prepared by blending 20 to 40 parts by weight of a brominated flame retardant (B) having a weight average molecular weight of 1000 to 5000, 6.0 to 15.0 parts by weight of an antimony compound (C), and 100 to 200 parts by weight of glass fiber (D) with 100 parts by weight of a polybutylene terephthalate resin having an intrinsic viscosity (A) of 0.50 to 1.00 dL / g.
[0015] In the thermoplastic resin composition, the combustion phenomenon occurs when the thermoplastic resin composition is exposed to a flame. The high-temperature thermoplastic resin starts thermal decomposition, and the combustible gas generated during this thermal decomposition continues to burn. Similarly, when polybutylene terephthalate resin is exposed to a flame and reaches a high temperature, the molecular chains are broken, generating combustible gas of low molecular weight components, which then burns. As a method of imparting flame retardancy to polybutylene terephthalate resin, in order to suppress the generation of combustible gas of low molecular weight components even when the molecular chains of polybutylene terephthalate resin are broken, it is preferable to use high molecular weight polybutylene terephthalate resin. However, when the polybutylene terephthalate resin has a high molecular weight, the fluidity during injection molding deteriorates. In addition, when glass fibers are highly filled to obtain high mechanical properties, the fluidity during injection molding further deteriorates, making it difficult to obtain good molded products.
[0016] The inventors of the present invention have found that by blending a large amount of glass fibers into a resin composition having no flame retardancy such as polybutylene terephthalate resin, the glass fibers exhibit the function as a flame retardant and suppress the combustion of combustible gas in the resin composition. Since glass fibers are incombustible materials of inorganic substances with a softening temperature of 700 °C or higher, it is considered that such a function is exhibited. In addition, since glass fibers are fibrous, it is considered that by orienting within the resin composition, the droplets of combustible components generated during the combustion of the resin composition are suppressed from dripping, and a resin composition having high flame retardancy can be obtained.
[0017] Here, the polybutylene terephthalate resin composition of the present invention contains (A) polybutylene terephthalate resin having an intrinsic viscosity of 0.50 to 1.00 dL / g, (B) a brominated flame retardant having a weight average molecular weight of 1000 to 5000, and (C) a reaction product obtained by reacting individual components with each other. However, since the reaction product is generated by a complex reaction between polymers, there are practical circumstances where it is not possible to specify its structure. Therefore, the present invention is specified by the components to be blended.
[0018] (A) A polybutylene terephthalate resin having an intrinsic viscosity of 0.50 to 1.00 dL / g The polybutylene terephthalate resin (A) having an intrinsic viscosity of 0.50 to 1.00 dL / g that constitutes the present invention (hereinafter, may be abbreviated as “(A) polybutylene terephthalate resin”) is a polymer obtained by a usual polymerization method such as polycondensation reaction of terephthalic acid or its ester-forming derivative and 1,4-butanediol or its ester-forming derivative, and in a range not impairing the properties, for example, when 100 parts by weight of the (A) polybutylene terephthalate resin is used, it may contain other copolymer components in an amount of about 20 parts by weight or less. Here, the main component referred to here means that, for each of the dicarboxylic acid component and the diol component, independently, terephthalic acid or its ester-forming derivative or 1,4-butanediol or its ester-forming derivative occupies more than 50 parts by weight when each of the components of the dicarboxylic acid component and the diol component is 100 parts by weight. Preferred examples of these polymers and copolymers include polybutylene terephthalate, polybutylene (terephthalate / isophthalate), polybutylene (terephthalate / adipate), polybutylene (terephthalate / sebacate), polybutylene (terephthalate / decanedicarboxylate), polybutylene (terephthalate / naphthalate), poly(butylene / ethylene) terephthalate, etc., and they may be used alone or in combination of two or more.
[0019] The amount of carboxyl groups in the (A) polybutylene terephthalate resin used in the present invention is preferably 40 eq / t or less from the viewpoints of hydrolysis resistance and heat resistance. From the viewpoint of hydrolysis resistance, it is more preferably 30 eq / t or less, and the lower limit value of the amount of carboxyl groups is about 0 eq / t. Here, the amount of carboxyl groups in the (A) polybutylene terephthalate resin is a value measured by titrating after dissolving the (A) polybutylene terephthalate resin in an o-cresol / chloroform solvent with ethanolic potassium hydroxide.
[0020] The method for producing the (A) polybutylene terephthalate resin used in the present invention is not particularly limited, and known polycondensation methods, ring-opening polycondensation methods, etc. can be used. Either a batch polycondensation method or a continuous polycondensation method may be used, and any of a method involving an ester exchange reaction and a polycondensation reaction, and a method by a polycondensation reaction by direct polymerization (direct polycondensation method) can be applied. The direct polycondensation method is preferable in terms of easy control of the amount of carboxyl end groups and economy.
[0021] In order to effectively promote the esterification reaction or the ester exchange reaction and the polycondensation reaction, it is preferable to add a catalyst during these reactions. Specific examples of the catalyst include organic titanium compounds such as methyl ester of titanic acid, tetra-n-propyl ester, tetra-n-butyl ester, tetraisopropyl ester, tetraisobutyl ester, tetra-tert-butyl ester, cyclohexyl ester, phenyl ester, benzyl ester, tolyl ester, or mixed esters thereof, dibutyltin oxide, methylphenyltin oxide, tetraethyltin, hexaethyldistannoxide, cyclohexhexyl distannoxide, didodecyltin oxide, triethyltin hydroxide, triphenyltin hydroxide, triisobutyltin acetate, dibutyltin diacetate, diphenyltin dilaurate, monobutyltin trichloride, dibutyltin dichloride, tributyltin chloride, dibutyltin sulfide, butylhydroxytin oxide, methylstannonic acid, ethylstannonic acid, butylstannonic acid and other alkylstannonic acids and other tin compounds, zirconia compounds such as zirconium tetra-n-butoxide, antimony compounds such as antimony trioxide, antimony acetate, etc. These catalysts can also be used in combination of two or more.
[0022] From the perspective of the carboxyl group concentration of the (A) polybutylene terephthalate resin used in the present invention, among these polymerization reaction catalysts, organic titanium compounds and tin compounds are preferred, and tetra-n-butyl ester of titanic acid is more preferably used. The addition amount of the catalyst is preferably in the range of 0.01 to 0.2 parts by weight with respect to 100 parts by weight of the (A) polybutylene terephthalate resin.
[0023] The (A) polybutylene terephthalate resin used in the present invention is characterized in that its intrinsic viscosity is 0.50 to 1.00 dL / g from the viewpoints of mechanical properties and fluidity. Preferably, it is 0.60 to 0.90 dL / g. When the intrinsic viscosity is less than 0.50 dL / g, the mechanical properties are significantly deteriorated. Further, when the intrinsic viscosity exceeds 1.00 dL / g, the fluidity becomes insufficient and it becomes difficult to obtain a good molded product. In the present invention, the intrinsic viscosity of the polybutylene terephthalate resin is a value measured at a temperature of 23 °C after dissolving the polybutylene terephthalate resin using an orthochlorophenol solution.
[0024] (B) Brominated flame retardant having a weight average molecular weight of 1000 to 5000 The (B) brominated flame retardant having a weight average molecular weight of 1000 to 5000 (hereinafter, may be abbreviated as "(B) brominated flame retardant") used in the present invention is not particularly limited as long as it is an organic compound containing bromine atoms added for the purpose of imparting flame retardancy to the resin. Specifically, brominated epoxy compounds, brominated polycarbonate compounds, brominated acrylate polymers, brominated polystyrene, brominated phthalimide, brominated polyphenylene ether, brominated imide, etc. may be mentioned. Two or more of these may be used. Further, the (B) brominated flame retardant preferably contains a brominated epoxy compound, a brominated polycarbonate compound and / or a brominated acrylate polymer, and more preferably contains at least one selected from brominated epoxy compounds and brominated polycarbonate compounds from the viewpoint of thermal stability.
[0025] The (B) brominated flame retardant used in the present invention is characterized in that the weight average molecular weight is 1000 to 5000 from the viewpoints of flame retardancy, mechanical properties, and fluidity. Preferably, it is 1500 to 4500, and more preferably, it is 2000 to 4000. When the weight average molecular weight of the (B) brominated flame retardant is less than 1000, the flame retardancy and thermal stability are significantly reduced. Further, when the weight average molecular weight of the (B) brominated flame retardant exceeds 5000, the fluidity becomes insufficient and it becomes difficult to obtain a good molded product. In the present invention, the weight average molecular weight of the (B) brominated flame retardant is determined as a value in terms of standard polystyrene measured by gel permeation chromatography (GPC) method.
[0026] The blending amount of the (B) brominated flame retardant having a weight average molecular weight of 1000 to 5000 in the polybutylene terephthalate resin composition of the present invention is in the range of 20 to 40 parts by weight with respect to 100 parts by weight of the polybutylene terephthalate resin having an intrinsic viscosity of 0.50 to 1.00 dL / g of the above (A). When the blending amount of the (B) brominated flame retardant having a weight average molecular weight of 1000 to 5000 is less than 20 parts by weight, the flame retardancy is insufficient. When the blending amount of the (B) brominated flame retardant having a weight average molecular weight of 1000 to 5000 exceeds 40 parts by weight, the productivity is significantly reduced.
[0027] (C) Antimony compound The (C) antimony compound used in the present invention is a compound containing an antimony atom, and by using it in combination with the (B) brominated flame retardant, the flammability of the resin composition can be improved. Representative examples of the (C) antimony compound include antimony trioxide, antimony tetroxide, antimony pentoxide, sodium antimonate, sodium pyroantimonate, etc., and one or more antimony compounds selected from these can be used. From the viewpoints of flame retardancy and mechanical properties, the (C) antimony compound preferably contains antimony trioxide, antimony tetroxide and / or antimony pentoxide, more preferably contains antimony trioxide and / or antimony pentoxide, and even more preferably contains antimony trioxide.
[0028] Although there is no particular limitation on the average particle size of the (C) antimony compound used in the present invention, it is preferably 0.1 to 5.0 μm, more preferably 0.3 to 4.5 μm. When the average particle size of the (C) antimony compound is within the above range, a high level of flame retardancy can be obtained with a relatively small addition amount, and as a result, excellent mechanical properties can be obtained when formed into a molded product.
[0029] The compounding amount of the (C) antimony compound in the polybutylene terephthalate resin composition of the present invention is characterized in that it is 6.0 to 15.0 parts by weight with respect to 100 parts by weight of the (A) polybutylene terephthalate resin. More preferably, it is 6.5 to 12.0 parts by weight. When the compounding amount of the (C) antimony compound is less than 6.0 parts by weight, the flame retardancy is significantly reduced. When the compounding amount of the (C) antimony compound exceeds 15.0 parts by weight, the fluidity and mechanical properties are significantly reduced.
[0030] (D) Glass fiber The (D) glass fiber used in the present invention is selected from glass compositions such as A glass, C glass, E glass, R glass, D glass, M glass, S glass, etc., and in particular, E glass is preferred. The (D) glass fiber is a chopped strand or roving type glass fiber usually used as a reinforcing material for PBT resin, and is preferably a glass fiber treated with a sizing agent containing a silane coupling agent such as an aminosilane compound or an epoxysilane compound and / or one or more epoxy compounds such as urethane, vinyl acetate, bisphenol A diglycidyl ether, novolac type epoxy compound, etc. Further, the above silane coupling agent and / or sizing agent may be used in an emulsion liquid.
[0031] The (D) glass fiber used in the present invention preferably has a fiber diameter of 1 to 15 μm, more preferably 5 to 14 μm, and even more preferably 6 to 13 μm. When the fiber diameter is 1 μm or more, the glass fiber length of the compound or the molded product after molding can be maintained to a certain extent, the reinforcing effect of the fiber can be obtained, and sufficient mechanical strength can be obtained. Further, by setting the fiber diameter of the (D) glass fiber to 15 μm or less, the number of glass fibers in the resin can be maintained while achieving the reinforcing effect of the resin, and sufficient mechanical strength can be obtained.
[0032] The compounding amount of the (D) glass fiber used in the present invention is characterized in that it is in the range of 100 to 200 parts by weight with respect to 100 parts by weight of the (A) polybutylene terephthalate resin. Preferably it is 125 to 175 parts by weight, and even more preferably 130 to 170 parts by weight. When the compounding amount of the (D) glass fiber is less than 100 parts by weight, sufficient mechanical strength and flame retardancy are not exhibited. Further, when it exceeds 200 parts by weight, the fluidity deteriorates and the productivity is significantly reduced.
[0033] (E) Anti-dripping agent The (E) anti-dripping agent used in the present invention is used to improve the flame retardancy of the resin composition. Examples thereof include silicone oil, reactive group-containing silicone oil, silica, and fluororesin, and fluororesin is particularly preferred. Specific examples of the fluororesin include fluororesins such as polytetrafluoroethylene, polyvinylidene fluoride, vinylidene fluoride / tetrafluoroethylene copolymer, and tetrafluoroethylene / hexafluoropropylene copolymer, or polymers obtained by polymerizing (meth)acrylic acid esters, aromatic alkenyl compounds, vinyl cyanide, etc. in the presence of polytetrafluoroethylene, etc., and powders obtained by compounding fluororesins with other polymers.
[0034] In the present invention, the blending amount of the (E) dripping inhibitor is preferably in the range of 1.0 to 2.0 parts by weight with respect to 100 parts by weight of the (A) polybutylene terephthalate resin. When the blending amount of the (E) dripping inhibitor is 1.0 part by weight or more, the expected dripping prevention effect is exhibited. When the blending amount of the (E) dripping inhibitor is 2.0 parts by weight or less, the fluidity can also be maintained.
[0035] [Other Components] In the polybutylene terephthalate resin composition of the present invention, other resin components, flame retardants other than the (B) brominated flame retardant and the (C) antimony compound, inorganic fillers other than the (D) glass fiber, mold release agents, phosphorus-based antioxidants, stabilizers, ultraviolet absorbers, colorants, lubricants, and other ordinary additives and a small amount of other types of polymers can be added as long as the effects of the present invention are not impaired.
[0036] The other resin components may be any melt-moldable resin other than the (A) polybutylene terephthalate resin composition, the (B) brominated flame retardant, the (C) antimony compound, and the (D) glass fiber. For example, AS resin (acrylonitrile / styrene copolymer), hydrogenated or non-hydrogenated SBS resin (styrene / butadiene / styrene triblock copolymer), hydrogenated or non-hydrogenated SIS resin (styrene / isoprene / styrene triblock copolymer), SEBS resin (hydrogenated styrene / butadiene / styrene triblock copolymer), polyethylene resin, polypropylene resin, polymethylpentene resin, cyclic olefin resin, cellulose resin such as cellulose acetate, polycarbonate resin, polyethylene terephthalate resin, polytrimethylene terephthalate resin, polyamide resin, polyacetal resin, polysulfone resin, polyphenylene sulfide resin, polyether ether ketone resin, polyimide resin, polyetherimide resin, etc. The resin to be mixed does not necessarily have to be one type, and two or more types may be used in combination.
[0037] In particular, amorphous resins such as AS resin (acrylonitrile / styrene copolymer) are easy to melt-knead with polybutylene terephthalate resin, and by blending them, molded articles with excellent dimensional stability can be produced.
[0038] (D) As inorganic fillers other than glass fiber, any filler such as fibrous, plate-like, powdery, or granular can be used. Specifically, fibrous or whisker-like fillers such as carbon fiber, rock wool, potassium titanate whisker, barium titanate whisker, aluminum borate whisker, silicon nitride whisker, and powdery, granular, or plate-like fillers such as mica, talc, kaolin, silica, calcium carbonate, glass beads, glass flakes, glass microballoons, clay, molybdenum disulfide, wollastonite, montmorillonite, titanium oxide, zinc oxide, calcium polyphosphate, graphite, barium sulfate, etc. can be mentioned. Two or more of these may be blended.
[0039] (B) As flame retardants other than brominated flame retardants and (C) antimony compounds, magnesium hydroxide hydrate, aluminum hydroxide hydrate, zinc hydroxystannate, zinc stannate, metastannic acid, tin oxide, tin oxide salt, zinc sulfate, zinc oxide, calcium borate hydrate, zinc borate, zinc borate hydrate, zinc oxide ferrous oxide hydroxide, ferric oxide, stannous oxide, stannic oxide, ammonium borate, ammonium octamolybdate, metal salts of tungstic acid, composite oxide acids of tungsten and metalloids, ammonium sulfamate, zirconium-based compounds, guanidine-based compounds, fluorine-based compounds, graphite, expanded graphite, etc. can be mentioned. Two or more of these may be blended.
[0040] As the release agent, any release agent used for the polybutylene terephthalate resin composition can be used. For example, plant waxes such as carnauba wax and rice wax, animal waxes such as beeswax and lanolin, mineral waxes such as montan wax, metal soaps such as lithium stearate and aluminum stearate, higher fatty acid amides such as ethylene bisstearylamide, petroleum waxes such as paraffin wax and polyethylene wax, etc. can be mentioned.
[0041] Examples of the phosphorus-based antioxidant include trisnonylphenyl phosphite, distearyl pentaerythritol diphosphite, etc.
[0042] As the stabilizer, benzotriazole-based compounds containing 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, as well as benzophenone-based compounds such as 2,4-dihydroxybenzophenone, phosphate esters such as mono- or distearyl phosphate and trimethyl phosphate, etc. can be mentioned.
[0043] Since these various additives may obtain a synergistic effect by combining two or more kinds, they may be used in combination.
[0044] In addition, for example, the additives exemplified as antioxidants may also act as stabilizers or ultraviolet absorbers. Also, among the ones exemplified as stabilizers, there are those having antioxidant or ultraviolet absorption effects. That is, the above classification is for convenience and does not limit the action.
[0045] Examples of the ultraviolet absorber include benzophenone-based ultraviolet absorbers typified by 2-hydroxy-4-n-dodecyloxybenzophenone, 2,2'-hydroxy-4,4'-dimethoxybenzophenone, bis(5-benzoyl-4-hydroxy-2-methoxyphenyl)methane, etc., and benzotriazole-based ultraviolet absorbers typified by 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-amylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-bis(α,α'-dimethylbenzyl)phenyl)benzotriazole, 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], condensate of methyl-3-[3-(2H-benzotriazol-2-yl-5-tert-butyl-4-hydroxyphenyl]propionate and polyethylene glycol, etc.
[0046] In addition, it may also include hindered amine-based light stabilizers typified by bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, tetrakis(2,2,6,6-tetramethyl-4-piperidyl)-1,2,3,4-butanetetracarboxylate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)-1,2,3,4-butanetetracarboxylate, poly{[6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethylpiperidyl)imino]hexamethylene[(2,2,6,6-tetramethylpiperidyl)imino]}, polymethylpropyl 3-oxy-[4-(2,2,6,6-tetramethyl)piperidinyl]siloxane, etc. Such light stabilizers exhibit better performance in terms of weather resistance, etc. when used in combination with the above ultraviolet absorbers and various antioxidants.
[0047] Examples of the colorant include organic dyes, organic pigments, inorganic pigments such as carbon black and titanium oxide, etc., and two or more of these may be blended.
[0048] Examples of carbon black include, but are not limited to, channel black, furnace black, acetylene black, anthracene black, lampblack, pine soot, and graphite. Carbon black having an average particle size of 500 nm or less and a dibutyl phthalate oil absorption of 50 to 400 cm 3 / 100 g is preferably used, and it may be treated with aluminum oxide, silicon oxide, zinc oxide, zirconium oxide, polyol, silane coupling agent, etc. as a treating agent.
[0049] Titanium oxide having a crystal form such as rutile form or anatase form and an average particle size of 5 μm or less is preferably used, and it may be treated with aluminum oxide, silicon oxide, zinc oxide, zirconium oxide, polyol, silane coupling agent, etc. as a treating agent.
[0050] Colorants such as organic dyes, organic pigments, carbon black, and titanium oxide may be used as a mixed material melt-blended or simply blended with various thermoplastic resins in order to improve the dispersibility with the polybutylene terephthalate resin composition of the present invention and the handleability during production. As the thermoplastic resin, polybutylene terephthalate resin is preferably used.
[0051] Examples of the lubricant include esters of fatty acids such as (poly)glycerin or (poly)pentaerythritol and aliphatic monocarboxylic acids such as caproic acid, enanthic acid, pelargonic acid, capric acid, octylic acid, lauric acid, myristic acid, behenic acid, palmitic acid, isostearic acid, stearic acid, oleic acid, isononanoic acid, alginic acid, montanic acid, etc.
[0052] Other examples include fluorescent brighteners, fluorescent dyes, flow modifiers, transesterification inhibitors, inorganic and organic antibacterial agents, photocatalytic antifouling agents, infrared absorbers, photochromic agents, etc.
[0053] The polybutylene terephthalate resin composition of the present invention is produced by a generally known method. For example, (A) polybutylene terephthalate, (B) a brominated flame retardant, (C) an antimony compound, (D) glass fiber and, if necessary, an inorganic filler other than glass fiber, an antioxidant, a lubricant, and, if further necessary, other necessary additives, colorants such as pigments and dyes are premixed or supplied to an extruder or the like without premixing and sufficiently melt-kneaded to prepare the polybutylene terephthalate resin composition of the present invention.
[0054] As an example of the above premixing, it is possible to simply dry blend, but examples include mixing using mechanical mixing devices such as tumblers, ribbon mixers, and Henschel mixers. Also, (D) glass fiber may be added by installing a side feeder in the feeding section and in the middle of the vent section of a multi-screw extruder such as a twin-screw extruder. Also, in the case of a liquid additive, it may be added using a plunger pump by installing a liquid addition nozzle in the feeding section and in the middle of the vent section of a multi-screw extruder such as a twin-screw extruder, or supplied by a metering pump from the feeding section or the like.
[0055] When producing the polybutylene terephthalate resin composition of the present invention, for example, a single-screw extruder, a twin-screw extruder, a triple-screw extruder, a conical extruder, and a kneader of the kneader type equipped with a screw of the "Unimelt" or "Damage" type can be used, but it is not limited thereto.
[0056] The polybutylene terephthalate resin composition thus obtained is injection molded by a generally known method to obtain the molded article of the present invention. As the above injection molding method, in addition to the ordinary injection molding method, a gas assist method, a two-color molding method, a sandwich molding, an in-mold molding, an insert molding, and an injection press molding are known, and any molding method can be applied.
[0057] The polybutylene terephthalate resin composition of the present invention can be used in various applications such as automotive parts, electrical and electronic parts, building members, various containers, daily necessities, miscellaneous goods for daily life, and sanitary products, and is particularly useful for molded products used as parts that require high mechanical strength and flame retardancy.
[0058] Specific applications include automotive underhood components such as air flow meters, air pumps, ignition bobbins, ignition cases, clutch bobbins, sensor housings, idle speed control valves, vacuum switching valves, ECU housings, inhibitor switches, rotation sensors, acceleration sensors, distributor caps, coil bases, actuator cases for ABS, air cleaner housings, brake booster parts, various cases, various tubes, various tanks, various hoses, various clips, various valves, various pipes, etc.; automotive interior components such as torque control levers, register blades, washer levers, window regulator handles, knobs for window regulator handles, passing light levers, sun visor brackets, various motor housings, etc.; automotive exterior components such as roof rails, fenders, garnishes, bumpers, door mirror stays, grille apron cover frames, lamp reflectors, lamp bezels, door handles, etc.; various automotive connectors such as wire harness connectors, SMJ connectors, PCB connectors, etc., electrical connectors, relay cases, coil bobbins, optical pickup chassis, motor cases, notebook computer housings and internal parts, CRT display housings and internal parts, printer housings and internal parts, mobile phone, mobile computer, handheld mobile, etc., housing and internal parts of portable terminals, housing and internal parts of recording media (CD, DVD, PD, FDD, etc.) drives, housing and internal parts of copiers, housing and internal parts of facsimiles, etc., electrical and electronic components represented by these; furthermore, video equipment components such as VTR parts, TV parts, irons, hair dryers, rice cooker parts, microwave oven parts, audio parts, video cameras, projectors, etc.; substrates of optical recording media such as LaserDisc (registered trademark), compact disc (CD), DVD-ROM, DVD-R, Blu-ray Disc, etc., lighting parts, refrigerator parts, air conditioner parts, etc., household and office electrical product parts represented by these.In addition, it is useful as electrical and electronic components such as housings and internal parts of electronic musical instruments, home game machines, portable game machines, various gears, various cases, sensors, connectors, sockets, resistors, relay cases, switches, coil bobbins, capacitors, optical pickups, oscillators, various terminal boards, printed wiring boards, speakers, headphones, small motors, magnetic head bases, power modules, semiconductors, liquid crystals, FDD chassis, motor brush holders, transformer members, etc., building members such as sash door cars, blind curtain parts, pipe joints, curtain liners, blind parts, gas meter parts, water meter parts, water heater parts, roof panels, ceiling hangers, etc., and mechanical parts such as bearings, levers, cams, ratchets, rollers, water absorption parts, toy parts, fans, cleaning jigs, motor parts, microscopes, binoculars, cameras, watches, etc. Since the resin composition of the present invention has both high mechanical strength and flame retardancy, among the above, it is particularly useful for automotive parts applications such as ignition bobbins, ignition cases, clutch bobbins, sensor housings, vacuum switching valves, ECU housings, vacuum pump cases, inhibitor switches, etc. and internal parts such as electrical connectors, relay cases, coil bobbins, optical pickup chassis, motor cases, notebook computer housings and internal parts, mobile phones, mobile computers, handheld mobiles, etc.
Examples
[0059] Hereinafter, the present invention will be described in more detail with reference to examples, but the present invention is not limited by these examples. The raw materials used in each example and comparative example are shown below.
[0060] (A) Polybutylene terephthalate resin (A-1) Polybutylene terephthalate resin, intrinsic viscosity 0.72 dL / g, carboxyl group content 15 eq / t, manufactured by Toray Industries, Inc. (A-2) Polybutylene terephthalate resin, intrinsic viscosity 0.85 dL / g, carboxyl group content 15 eq / t, manufactured by Toray Industries, Inc. (A'-1) Polybutylene terephthalate resin, intrinsic viscosity 1.25 dL / g, carboxyl group content 22 eq / t, manufactured by Toray Industries, Inc.
[0061] (B) Brominated flame retardant (B-1) Brominated polycarbonate compound: Tetrabromobisphenol-A-polycarbonate oligomer ("Firegard" (registered trademark) FG-8500 (product name), weight average molecular weight 3000, manufactured by Teijin Limited). (B-2) Brominated epoxy compound: Tetrabromobisphenol-A-epoxy oligomer with tribromophenol end groups (manufactured by DIC Corporation, ECX-30 (product name), weight average molecular weight 3800). (B'-1) Brominated epoxy compound: Tetrabromobisphenol-A-epoxy oligomer with tribromophenol end groups (manufactured by Sakamoto Yakuhin Kogyo Co., Ltd., SR-T3040 (product name), weight average molecular weight 6000). (B'-2) Brominated epoxy compound: Tetrabromobisphenol-A-epoxy oligomer with epoxy end groups (manufactured by Sakamoto Yakuhin Kogyo Co., Ltd., SR-T5000 (product name), weight average molecular weight 10000).
[0062] (C) Antimony compound (C-1) Antimony trioxide (manufactured by Nippon Seiko Kogyo Co., Ltd., PATOX-MK (product name)). (C-2) Antimony tetroxide (manufactured by Yamanaka Sangyo Co., Ltd., ATE-H (product name)). (C-3) Antimony pentoxide (manufactured by Yamanaka Sangyo Co., Ltd., HY-1030 (product name)).
[0063] (D) Glass fiber (D-1) Chopped strand glass fiber (manufactured by Nippon Electric Glass Co., Ltd., T-187 (product name), 3 mm long, average fiber diameter 13 μm). (D-2) Chopped strand glass fiber (manufactured by Nippon Electric Glass Co., Ltd., T-187H (product name), 3 mm long, average fiber diameter 10 μm).
[0064] (E) Dripping inhibitor (E-1) Acrylic-modified polytetrafluoroethylene (manufactured by Mitsubishi Chemical Corporation, Metablen (registered trademark), A-3800 (product name)).
[0065] (F) Release agent (F-1) Ethylene bisstearylamide (manufactured by Palmamide, "PALMOWAX" (registered trademark) EBS-SF (product name)).
[0066] [Examples 1 to 12, Comparative Examples 1 to 10] According to the compounding compositions shown in Table 1, (A) polybutylene terephthalate, (B) brominated flame retardant, (C) antimony compound, (E) anti-dripping agent, and (F) release agent were supplied from the hopper part of a twin-screw extruder, and (D) glass fiber was supplied from a secondary hopper installed between the main inlet and the tip of the extruder, and melt-kneading was carried out using a twin-screw extruder (manufactured by Toshiba Machine Co., Ltd., TEM37SS (product name)) with a screw diameter of 37 mmφ set at a cylinder temperature of 260°C. The strands discharged from the die were cooled in a cooling bath and then pelletized with a strand cutter to obtain a resin composition. The results of evaluating the obtained resin composition by the above method are shown in Table 1.
[0067] The evaluation methods in the examples and comparative examples are summarized below.
[0068] (1) Productivity The pelletization ease of the resin compositions of the examples and comparative examples was evaluated. A compounding composition that could be pelletized without problems was judged as ○, and a compounding composition in which the state of the strands discharged from the die was unstable and could not be taken up and pelletization was impossible was judged as ×.
[0069] (2) Tensile properties After drying the resin composition pellets obtained in each example and comparative example in a hot air dryer at 130 °C for 3 hours or more, using a SE50DUZ type injection molding machine manufactured by Sumitomo Heavy Industries, Ltd., under the molding conditions of a cylinder temperature of 260 °C and a mold temperature of 80 °C, a multi-purpose test piece type A (total length 150 mm, width of test part 10 mm, thickness 4 mm) specified in ISO 3167:2002 was created by injection molding. Using the obtained test pieces, the tensile properties were measured according to ISO 527-1, -2:2012.
[0070] (3) Flexural properties After drying the resin composition pellets obtained in each example and comparative example in a hot air dryer at 130 °C for 3 hours or more, using a SE50DUZ type injection molding machine manufactured by Sumitomo Heavy Industries, Ltd., under the conditions of a cylinder temperature of 260 °C and a mold temperature of 80 °C, a multi-purpose test piece type A (total length 150 mm, width of test part 10 mm, thickness 4 mm) specified in ISO 3167:2002 was molded. Using five of each of the obtained test pieces, the flexural modulus was measured in accordance with ISO 178:2001.
[0071] (4) Charpy impact strength After drying the resin composition pellets obtained in each example and comparative example in a hot air dryer at 130 °C for 3 hours or more, using a SE50DUZ type injection molding machine manufactured by Sumitomo Heavy Industries, Ltd., under the conditions of a cylinder temperature of 260 °C and a mold temperature of 80 °C, a multi-purpose test piece type A (total length 150 mm, width of test part 10 mm, thickness 4 mm) specified in ISO 3167:2002 was molded. For each of the 10 obtained test pieces, a notch was made so that 8 mm remained in the strip test piece (80 mm × 10 mm × 4 mm) cut out from the parallel part, and the Charpy impact strength was measured in accordance with ISO 179:2010.
[0072] (5) Flammability After drying the resin composition pellets obtained in each example and comparative example in a hot air dryer at 130°C for 3 hours or more, a rod-shaped test piece (125 mm × 13 mm × 0.75 mm thickness) was produced using a SE50DUZ injection molding machine manufactured by Sumitomo Heavy Industries, Ltd. The injection conditions were a cylinder temperature of 260°C and a mold temperature of 80°C. The obtained test pieces were measured for 50W (20 mm) vertical flammability in accordance with UL-94. The test was carried out using a total of 10 test pieces, 5 test pieces left standing in an environment of 23°C and 50% RH for 48 hours and 5 test pieces left standing in an environment of 70°C for 168 hours and then left stationary in a desiccator for 4 hours or more. Judgments of V-0, V-1, V-2, and V-out were made in accordance with UL-94, and the number of melt drippings onto the cotton placed under the test piece during the flammability test was evaluated.
[0073] (6) Fluidity Using a strip-shaped molded product with a thickness of 1 mm and a width of 10 mm, it was judged by the flow length. The flow length was taken as the length of the above strip-shaped molded product obtained by injection molding the polybutylene terephthalate resin composition of the compositions of the examples and comparative examples using a NEX1000 injection molding machine manufactured by Nissei Plastic Industrial Co., Ltd. The injection conditions were a cylinder temperature of 260°C, a mold temperature of 80°C, an injection pressure of 80 MPa, an injection time of 8 seconds, and a cooling time of 8 seconds.
[0074] [Table 1]
[0075] It is clear from Table 1 as follows.
[0076] From the comparison between Examples 1 to 12 and Comparative Examples 1 to 10, it can be seen that the polybutylene terephthalate resin composition comprising (A) 100 parts by weight of a polybutylene terephthalate resin having an intrinsic viscosity of 0.50 to 1.00 dL / g, (B) 20 to 40 parts by weight of a brominated flame retardant having a weight average molecular weight of 1000 to 5000, (C) 6.0 to 15.0 parts by weight of an antimony compound, and (D) 100 to 200 parts by weight of glass fiber is excellent in productivity, mechanical properties, flame retardancy, and fluidity. In particular, by using (D) glass fiber within the range of 100 to 200 parts by weight, not only excellent mechanical properties can be obtained, but also the glass fiber exhibits the function as a flame retardant, and it can be said that the flame retardancy is also excellent.
Claims
1. A polybutylene terephthalate resin composition comprising: (A) 100 parts by weight of a polybutylene terephthalate resin having an intrinsic viscosity of 0.50 to 1.00 dL / g; (B) 20 to 40 parts by weight of a brominated flame retardant having a weight average molecular weight of 1000 to 5000; (C) 6.0 to 15.0 parts by weight of an antimony compound; and (D) 100 to 200 parts by weight of glass fiber.
2. The polybutylene terephthalate resin composition according to claim 1, wherein the (C) antimony compound is antimony trioxide.
3. The polybutylene terephthalate resin composition according to claim 1 or 2, wherein the (B) brominated flame retardant having a weight average molecular weight of 1000 to 5000 is at least one selected from a brominated polycarbonate compound and a brominated epoxy compound.
4. The polybutylene terephthalate resin composition according to claim 1 or 2, wherein the amount of the (D) glass fiber is 125 to 175 parts by weight with respect to 100 parts by weight of the (A) polybutylene terephthalate resin having an intrinsic viscosity of 0.50 to 1.00 dL / g.
5. The polybutylene terephthalate resin composition according to claim 1 or 2, further comprising (E) 1.0 to 2.0 parts by weight of an anti-dripping agent with respect to 100 parts by weight of the (A) polybutylene terephthalate resin having an intrinsic viscosity of 0.50 to 1.00 dL / g.
6. A molded article made of the polybutylene terephthalate resin composition according to claim 1 or 2.
Citation Information
Patent Citations
Flame-retarding aromatic polyester resin composition
JP1991296560A
Thermoplastic resin composition
JP1997194695A
Fiber-reinforced flame-retardant thermoplastic resin composition, molded article and method for producing fiber-reinforced flame-retardant thermoplastic resin composition
JP2012214819A